A institucionalização do atendimento educacional especializado (aee) em um município da região central do estado do Rio Grande do Sul - Gattiboni, Bruna Dalcin (2017)
This research is linked to the Professional Master‟s Degree of the Graduate Program in Public Policies and Educational Management of the Federal University of Santa Maria (UFSM), in the research line of Public Policies for Basic Education. The purpose of this study was to investigate the public school management process and its implications over the policies for inclusive education policies. The investigative course is based on qualitative-quantitative research, bringing elements that complement each other, corroborating for a more comprehensive interpretation of the studied reality. The information search went through theoretical references collection from legal documents and through authors that raise discussions about the concept of democratic management, the theoretical plurality and its role on the processes of social reproduction in inclusive education. In this way, it was used semi-structured interviews for data collection, carried out with twelve teachers from some Brazilian public schools located in the state of Rio Grande do Sul. Data analysis focused on the search for discursive recurrences from the semi-structured interviews and, as strategy, it was conducted the analysis of the Political Pedagogical Projects of the schools. From this perspective, as a conclusion, I could see that the institutionalization of the Specialized Educational Attendance (SEA) in the given schools in Rio Grande do Sul is at the beginning and it is moving slowly towards what we name inclusion education. Also, that little is discussed about effective educational inclusion thus passing the responsibility of student‟s inclusion to the SEA worker. Finally, I emphasize the importance of the discussion on the subject, and I see this thesis as a product from the trajectory covered within Master Degree, where there were some discussions about Specialized Educational Attendance, inclusive education and also on democratic school management.